2020
DOI: 10.1371/journal.pone.0244270
|View full text |Cite
|
Sign up to set email alerts
|

Massachusetts general hospital Covid-19 registry reveals two distinct populations of hospitalized patients by race and ethnicity

Abstract: Objective To evaluate differences by race/ethnicity in clinical characteristics and outcomes among hospitalized patients with Covid-19 at Massachusetts General Hospital (MGH). Methods The MGH Covid-19 Registry includes confirmed SARS-CoV-2-infected patients hospitalized at MGH and is based on manual chart reviews and data extraction from electronic health records (EHRs). We evaluated differences between White/Non-Hispanic and Hispanic patients in demographics, complications and 14-day outcomes among the N = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Conversely, in other cohort studies, Ogedegbe et al [ 14 ], Kabarriti et al [ 15 ], and Rodriguez et al [ 16 ] reported that the rates of adverse outcomes of COVID-19 did not differ by race/origin after adjustment for sociodemographic and clinical characteristics. Consistent with this evidence, Bassett et al [ 18 ] showed that Hispanic/Latin American patients had fewer comorbidities, but comparable rates of ICU admission and death [ 18 ]. Globally, we can deduce that the higher crude mortality seen in Latin Americans is not generally confirmed after adjusting for COVID-19-cause-of-death.…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, in other cohort studies, Ogedegbe et al [ 14 ], Kabarriti et al [ 15 ], and Rodriguez et al [ 16 ] reported that the rates of adverse outcomes of COVID-19 did not differ by race/origin after adjustment for sociodemographic and clinical characteristics. Consistent with this evidence, Bassett et al [ 18 ] showed that Hispanic/Latin American patients had fewer comorbidities, but comparable rates of ICU admission and death [ 18 ]. Globally, we can deduce that the higher crude mortality seen in Latin Americans is not generally confirmed after adjusting for COVID-19-cause-of-death.…”
Section: Discussionmentioning
confidence: 76%
“…This retrospective observational study included adults with confirmed COVID-19 infection who met criteria for inpatient admission at the Massachusetts General Hospital between March 8 to April 27, 2020 [12]. We excluded patients with active cancer except non-melanoma ).…”
Section: Study Populationmentioning
confidence: 99%
“…We performed a matched cohort study using data from the MGH COVID-19 Data Registry for confirmed SARS-CoV-2 infected patients hospitalized at MGH. 4 The registry included 866 COVID-19 inpatients (hospitalized March 8, 2020, to April 27, 2020) and was created using both manual chart review and coded data extraction from the electronic health record in the Mass General Brigham Enterprise Data Warehouse. Trained chart reviewers extracted demographics, comorbid conditions, intensive care unit (ICU) admission, clinical complications, and death.…”
mentioning
confidence: 99%